Inventarisasi Jenis-Jenis Mangrove yang Ditemukan di Kawasan Tanjung Bila Kecamatan Pemangkat Kabupaten Sambas - Elvi Rusmiyanto Pancaning Wardoyo, Dekky, Riza Linda (Jurnal Protobiont, 2016)
Mangrove is a community of tropical coastal plants dominated by several species of trees with shrubs that have the ability to grow in coastal areas. The purpose of this research is to know various kind of mangroves which located in Tanjung Bila area. The research were done for 4 month start from February until May 2016 in Tanjung Bila Pemangkat region Sambas regency. The data of mangrove vegetation were collected using the transect line plot method. There were 8 species of mangroves found in Tanjung Bila area and classified into 5 family i.e. Avicennia marina, Avicennia alba (Avicenniaceae), Bruguiera cylindrica, Rhizophora apiculata (Rhizophoraceae), Sonneratia caseolaris (Sonneratiaceae), Acanthus ilicifolius, Acanthus volubilis (Acanthaceae) dan Acrostichum speciosum (Pteridaceae).